Analisis Perbandingan Kerentanan Financial Distress PT. Garuda Indonesia Tbk dan PT. Indonesia Airasia Tbk Melalui Pendekatan Modifikasi Altman Z-Score - Agus Kurniawan; Diah Permata Sari; Rani Sri Sumarsih (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study examines the main issues related to the escalation of global Maintenance, Repair, and Overhaul (MRO) costs in 2025, reaching 20.14% of total operational expenses, thus threatening the financial stability of national airlines. This study aims to analyze and compare the level of financial distress vulnerability at PT Garuda Indonesia (Persero) Tbk (GIAA) and PT Indonesia AirAsia Tbk (CMPP). The theoretical basis used in detecting this risk is Signal Theory. The novelty of this study lies in the comparative evaluation of the resilience of Full-Service Carrier (FSC) and Low-Cost Carrier (LCC) business models in facing post-pandemic spare parts supply chain disruptions in 2025. The methodology used is descriptive quantitative with a comparative approach to the financial statements of the first quarter of 2025. The statistical tool used to process financial ratios is Microsoft Excel 2021 through the Modified Altman Z-Score formula. The results show that both airlines are absolutely in the Distress Zone with values ​​below the threshold of 1.1. GIAA is in a state of technical bankruptcy due to liquidity pressure from historical debt burden with a Z-Score of 0.0460, while CMPP is facing fatal equity erosion due to accumulated losses exceeding the value of its total assets with a negative Z-Score of -1.7400.